Characteristics of Varicose Vein Patients Underwent Endovenous Laser Ablation (EVLA) in Vascular and Endovascular Surgery Sub-Division of Dr. Mohammad Hoesin General Hospital Palembang between January 2019 - December 2019 - Deo Valendra; Kemas Muhammad Dahlan (Sriwijaya Journal of Surgery, 2021)
Background: Chronic venous disease is often overlooked by health care providers because it has mild symptoms and low mortality. The most common manifestations of chronic venous disease are varicose veins. Risk factors for varicose veins are multifactorial. We aim to determine the characteristics of varicose vein patients who underwent endovenous laser ablation (EVLA). Methods: This research is a retrospective descriptive study and was conducted in January 2019 - December 2019 at the Vascular and Endovascular Surgery Sub-division of the General Hospital dr. Mohammad Hoesin Palembang. The samples were all of varicose vein patients who underwent EVLA and was collected with total sampling. The variables used include age, gender, level of severity/grading, and management. The data obtained were processed descriptively and were presented in tabular and narration. Results: There were 24 subjects meeting research critera. The highest age group for varicose veins was in the age group 55 to 74 years as many as 11 people (45.8%). The most varicose vein patients were found in male as many as 14 people (58.3%). Based on the grading of severity, most were in grade C5, namely 14 people (58.3%). In varicose vein patients based on the type of intervention, the most cases occurred with EVLA and phlebotomy as many as 22 people (91.7%). Most subjects did not experience postoperative recanalization, namely 22 people (91.7%). Conclusion: Male patients aged 55 to 74 years old, with severity grade of C5, treated with EVLA and phlebotomy, and without post-operative complication of recanalization are all the most common characteristics of varicose veins patients in dr Mohammad Hoesin General Hospital Palembang.